2010
DOI: 10.1007/s11999-009-1172-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Function after Arthroscopic Partial Meniscectomy

Abstract: Background Quadriceps muscle strength, which is essential for the function and stability of the knee, has been found to be impaired even years after arthroscopic partial meniscectomy. However, the neuromuscular alterations that could account for such muscle weakness remain unclear. Questions/purposes We investigated (1) the side-to-side asymmetries in quadriceps muscle strength 6 months after arthroscopic partial meniscectomy, (2) the physiologic mechanisms (neural versus muscular) underlying muscle weakness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…We attempted to contact via e-mail authors of 3 studies that only reported means and standard deviations in figures. 12,13,15 If we could not contact authors after several attempts, we excluded studies that did not report specific numeric means and standard deviations ( Figure 1). 12,15 Previously unpublished data were secured from 1 of the authors 13 contacted, resulting in 4 studies 3,9,11,13 included in our final analysis.…”
Section: Evidence Synthesis Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We attempted to contact via e-mail authors of 3 studies that only reported means and standard deviations in figures. 12,13,15 If we could not contact authors after several attempts, we excluded studies that did not report specific numeric means and standard deviations ( Figure 1). 12,15 Previously unpublished data were secured from 1 of the authors 13 contacted, resulting in 4 studies 3,9,11,13 included in our final analysis.…”
Section: Evidence Synthesis Search Resultsmentioning
confidence: 99%
“…The skewedness of the funnel plot may be attributed to smaller studies with greater variability showing the largest effect sizes. 22 Among the studies we included in our analyses, the studies with the largest 11 and smallest 13 sample size appeared toward the base of our funnel with small effect sizes. Furthermore, the Gapeyeva et al 3 study appearing at the top of the funnel plot incorporated the smallest sample size and exhibited the greatest variance, likely contributing to the skewed nature of the funnel plot.…”
Section: Quality and Publication Bias Assessmentmentioning
confidence: 97%
See 2 more Smart Citations
“…42 Despite the minimally invasive nature, studies have shown that patients undergoing arthroscopic meniscectomy have pain, effusion, loss of range of motion (ROM), functional changes, neuromuscular and biomechanical changes, loss of quadriceps muscle strength, and a reduced quality of life. 5,8,12,13,27,30,31,33 Herrlin et al 17 showed that for middleaged patients with simple lesions in the meniscus, physical therapy has yielded T T STUDY DESIGN: Systematic review with metaanalysis.…”
mentioning
confidence: 99%